Pandemic's impact on education - Corina Georgeta Dinculescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
In a world crisis generated by the spread of Covid-19, beyond the negative consequences, fast and efficient responses were needed from the authorities across the world, both for the scenario in which the crisis was on a short period and education would have recovered quickly, and especially for the scenario in which the crisis persisted for a longer period (several months), and in this case the solutions should provide equal access to education for all children and young people. We are still in the second scenario, and during this time momentary solutions have been found, yet far from being efficient and sufficient. At the beginning of pandemics, school closure was considered necessary by the authorities throughout the world, including Romania. On the long term, this action has had, and will continue to have negative effects on education, mainly for vulnerable and marginalised children and young people: the disappearance of direct learning opportunities (which can create serious inequality of opportunity), a high school dropout rate, etc. Most school systems in the world have offered various ways of distance (online) learning, but some of them could not be applied in certain areas or in the case of certain categories of children/young people, due to limited access to internet and to a personal computer/tablet from home. Romania also embraced this idea, yet in practice the online teaching modalities have been extremely low (insufficiently trained teaching staff in using digital systems for online education and pedagogy, as well as in developing online teaching tools, insufficient platforms with free use - without cost to be used for online lessons, etc.). This paper attempts to highlight the challenges that the education systems had to face as a result of the health crisis that began in early 2020 (which still continues, provided that the threat of infection has not disappeared yet). Another objective was to identify the solutions adopted by authorities to reduce the negative impact on education, avoiding the increase of discrimination of the already disadvantaged categories of persons, in particular (children and young people coming from low-income families, disabled children and young persons, with learning difficulties, etc.), as well as the disparities between residence areas.
Keywords: I21; I24; J14; J15; R11; 330; education; online learning; inequalities in education; urban-rural disparities